Social Culture and Localism of Mee Tribe In Knowing Noken At Beko Village Obano District Regency Paniai, Province of Papua - Irnawati, Irnawati; Maruapey, Azis; Ohorella, Syarif; Febriadi, Ihsan; Jeni Maipauw, Niny (KnE Social Sciences, 2023)
The purpose of this research is plants as raw materials for making noken in Beko Village, Obano District, Paniai Regency.. The method used in this research was descriptive method with Focus Group Discussion (FGD) approach. The results of the study that Noken is the result of cultural arts are owned by the Mee Tribe, especially women, which at the same time symbolize the values and socio-cultural functions. The Mee localism in making Noken by utilizing planst bark includes the Melinjo tree (Damiyo), Ilam tree bark (Tokeipo), anyamin tree (Kepiyai), tree bark (Woge), Watu tree bark and Epiyo which is still easy with the level of vegetation category poles with diameters between 10-20 cm. The traditional raw material treatment of large Noken by the Mee tribe in Beko village is by way of Melinjo bark (Damiyo), Ilam bark (Tokeipo), anyamin tree (Kepiyai), bark (Woge), Watu and Epiyo tree bark drying, smoothing bark and coloring. The process of making Noken follows the embroidery and woven pattern, types of local plants namely Takai and Tokeipo. Noken knitting process is done when relaxing or resting, where large Noken knitting can be at home, market or meeting place in the village. Keywords: Social culture, Localism, Noken, Mee tribe